2015
DOI: 10.1161/circinterventions.114.001813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Histopathologic Analysis Following Renal Sympathetic Denervation Over Multiple Time Points

Abstract: Background-The pathology of radiofrequency-derived sympathetic renal denervation has not been studied over time and may provide important understanding of the mechanisms resulting in sustained blood pressure reduction. The purpose of this study was to investigate chronological changes after radiofrequency-renal denervation in the swine model. Methods and Results-A total of 49 renal arteries from 28 animals with 4 different time points (7, 30, 60, and 180 days) were examined. Semiquantitative histological ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 22 publications
8
41
1
Order By: Relevance
“…These features are consistent with the current literature describing the histopathologic observations following RF ablation with other devices. 14,17,18 Effective RF nerve ablation has been previously shown to decrease NE levels in large animal models. 19,20 In this study, the norepinephrine levels measured in the single ablation animals demonstrated a significant NE decrease at all time points compared to naïve kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…These features are consistent with the current literature describing the histopathologic observations following RF ablation with other devices. 14,17,18 Effective RF nerve ablation has been previously shown to decrease NE levels in large animal models. 19,20 In this study, the norepinephrine levels measured in the single ablation animals demonstrated a significant NE decrease at all time points compared to naïve kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the Simplicity renal ablation system was used to investigate chronological changes in the renal arteries after radiofrequency renal denervation in the swine model (75). A total of 49 renal arteries from 28 animals with 4 different time points (7, 30, 60, and 180 days) were examined.…”
Section: Other Potential Determinants Of the Antihypertensive Responsmentioning
confidence: 99%
“…Short-term 6 month Bp results or incomplete follow-up (34) cannot be extrapolated into durability of the Bp response or the prevention of cardiovascular complications. This is particularly the case in view of a recent report describing renal reinnervation within 60 days after renal nerve ablation in an experimental model (35). The DENERHTN investigators will soon report whether or not the need to continue or intensify antihypertensive drug treatment after RDN limits the cost-effectiveness of the procedure (9).…”
Section: -H Sbpmentioning
confidence: 99%